Recreating Europe : the European Union's policy towards Central and Eastern Europe - Mayhew, Alan (Cambridge : Cambridge University Press, 1998)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: economische verhoudingen; Europese Unie (EU).